Dilema Karyawan Milenial: Mengelola Konflik Kerja Keluarga untuk Kinerja Optimal - Vicencia Valendinata; Yanuar (Jurnal Ekonomi, 2025)
This study investigates the impact of the work environment, job security, and work-family conflict on the performance of Millennial and Gen Z employees, with employee engagement as a mediating variable. A quantitative descriptive method was used, with data collected through a Google Form questionnaire targeting employees aged 18 to 43 at PT. XY. A total of 112 samples were gathered using purposive sampling and analyzed using PLS-SEM with Smart-PLS 4.0. The results indicate that the work environment, job security, and work-family conflict significantly influence employee engagement and performance. Employee engagement also positively affects performance and mediates the relationship between the independent variables and performance. This study expands previous research by incorporating employee engagement as a mediating variable within the JD-R and Employee Engagement theories. While job resources enhance engagement and performance, job demands hinder both, emphasizing the critical role of employee engagement in improving young employees' performance.